Note sulla fanciullezza nel pensiero di Leopardi - Michele Zedda (Firenze University Press, 2015)
Childhood is a central topic in Leopardi's literary production. The poet describes the child's mind very carefully: his memory, imagination, attention and his pe- culiar points of view. These descriptions haven't a direct pedagogical purpose, but it is possible to find in them important ideas on education.